Analysis of basic release techniques in archery athletes - Betrix Teofa Perkasa Wibafied Billy Yachsie (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Archery is an individual sport that requires consistent technique therefore this study aims to determine how good the basic archery techniques are for the male and female athletes of the archery club in Banyumas with a quantitative descriptive design using descriptive methods. The research population is archery athletes at the Taurus Archery School club, a total of 28 athletes. Samples were taken using purposive sampling totaling 14 athletes, with criteria for male and female adolescent athletes not in a state of illness. The instrument used is a Rubik or an assessment sheet by observing the object under study and analyzing using descriptive percentages. The results of the research on basic archery techniques for male athletes in the very poor category are 0.00% (0 athletes), less 71.43% (5 athletes), good 28.57% (2 athletes), and very good 0. 00% (0 athletes). While the basic archery techniques for female athletes are in the very poor category of 0.00% (0 athletes), less than 100.00% (7 athletes), good 0.00% (0 athletes), and very good 0.00% (0 athletes). Based on the average value of basic archery techniques for female athletes of the Taurus Archery School club in the less category.